MENYOAL KEMBALI REFORMASI BIROKRASI DI INDONESIA - Rahmatunnisa, Mudiyati (Governance, 2010)
This paper is aimed at analyzing public sector reform as a globalized movement and its practices in Indonesia. It is argued that normatively, it must be admitted that the reform process, started since the fall of Suharto?s New Order regime in the late 1990s, has shown significant progress. Nevertheless, empirically, the process has not brought similar progress particularly in terms of eradicating abused of power and delivering sophisticated public services.